Trauma and Transgression in Nature-Based Leisure - Dietsch, Alia M.; Jazi, Everly; Floyd, Myron F.; Ross-Winslow, Danielle; Sexton, Natalie R. (Frontiers in Sports and Active Living, 2021)
Time spent engaged in nature-based leisure activities (e.g., hiking, picnicking, hunting, fishing) can improve physical health, cognitive functioning, and emotional wellbeing, among other benefits. However, in the United States (U.S.), evidence overwhelmingly demonstrates differences in who uses federal public lands where nature-based leisure is welcomed when consistent with institutional goals, suggesting inequities regarding who benefits from nature-based leisure on public lands. Previous research efforts have uncovered numerous intrapersonal, interpersonal, and institutional reasons (i.e., constraints) for why not all peoples can access or feel comfortable and safe accessing nature-based spaces. In addition to contemporary constraints on participation, historical policies and practices, including slavery, forced migration, de jour segregation, environmental racism, and more, have resulted in trauma that can influence people’s relationship to nature. Many marginalized peoples have also ‘transgressed’ historical practices of terror or exclusion by using nature-based spaces to escape oppression, challenge oppressive practices, and to commune with nature, oneself, or one’s community. To better understand constraints on the nature-based leisure activity of diverse audiences, we synthesize discussions held as part of community workshops at National Wildlife Refuges proximate to urban areas across the U.S. We specifically use co-cultural theory to uncover the trauma and transgressions voiced by participants as part of these discussions. This work underscores ways in which minoritized peoples have (re)claimed nature-based spaces despite oppression and deep-rooted traumas, offering stories of hope and pride from which dominant institutions, such as public lands agencies, can learn. Uplifting and promoting these stories of transgression, and addressing the deep-rooted trauma that exists, can ultimately fulfill the rights of all to enjoy the health benefits that nature-based leisure can provide.